Non-coding RNAs: The recently accentuated molecules in the regulation of cell autophagy for ovarian cancer pathogenesis and therapeutic response - Peng, Bi; Li, Jing; Yan, Yuanliang; Liu, Yuanhong; Liang, Qiuju; Liu, Wei; Thakur, Abhimanyu; Zhang, Kui; Xu, Zhijie; Wang, Jian; Zhang, Fan (Frontiers in Pharmacology, 2023)
Autophagy is a self-recycling and conserved process, in which the senescent cytoplasmic components are degraded in cells and then recycled to maintain homeostatic balance. Emerging evidence has suggested the involvement of autophagy in oncogenesis and progression of various cancers, such as ovarian cancer (OC). Meanwhile, the non-coding RNAs (ncRNAs) frequently regulate the mRNA transcription and other functional signaling pathways in cell autophagy, displaying promising roles in human cancer pathogenesis and therapeutic response. This article mainly reviews the cutting-edge research advances about the interactions between ncRNAs and autophagy in OC. This review not only summarizes the underlying mechanisms of dynamic ncRNA-autophagy association in OC, but also discusses their prognostic implications and therapeutic biomarkers. The aim of this review was to provide a more in-depth knowledge framework exploring the ncRNA-autophagy crosstalk and highlight the promising treatment strategies for OC patients.